MANAJEMEN KEUANGAN KELUARGA - Leny Nofianti; Angrieta Denziana (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
The housewife generally represents as a menager in managing family finance. There are several key concepts of family finance management which is important to know in order to manage the family finance professionally. They are balance and loss/profit and also the management of cashflow. With the existence of a good understanding about family financial report, supported by good planning, division of duty with couple and effort of interrogating the extra of expenditure, hence the domestic can through the family finance problem with the correct solution. The most important thing is openness each other and also experiences the family life responsibility with.